Screening and exploration of neoadjuvant “de-escalation” therapy for early breast cancer - Zhang, Nana; Shan, Ming; Huang, Zhenfeng; Gao, Fei; Xu, Bingqi; Kang, Wenli; Zhang, Jian; Song, Li; Liu, Jun; Zhang, Jiawei; Liu, Mingyang; Jiang, Haitao; et al. (Frontiers in Pharmacology, 2025)
BackgroundNeoadjuvant therapy for breast cancer improves the prognosis of high-risk patients. However, whether pathological completed response (pCR) can be used as a surrogate endpoint for de-escalation therapy in patients who are relatively sensitive to treatment remains to be elucidated.MethodsWe retrospectively reviewed 143 breast cancer patients, with clinical stage (cStage) II–IIIA who received neoadjuvant chemotherapy and achieved pCR in a short time (within 16 weeks) from 2012 to 2022. The prognosis of patients was analysed using the Kaplan-Meier method, Cox proportional hazards regression models to identify independent clinicopathologic factors affecting prognosis.ResultsThe median follow-up period was 47 months, the overall 4-year disease-free survival (DFS) and overall survival (OS) were 95.3% and 96.9%, respectively, in 143 patients with pCR after neoadjuvant chemotherapy. The 4-year DFS between the postoperative adjuvant chemotherapy and no adjuvant chemotherapy groups was 76.4% and 95.2%, with a significant statistical difference between both groups (P < 0.05). For HER2-positive (HER2+) and Triple negative breast cancer (TNBC), the addition of targeted therapy or platinum-based drugs had no impact on prognosis. Univariate and multivariate analyses of prognosis showed that only postoperative adjuvant chemotherapy significantly affected prognosis.ConclusionPatients with operable cStage II–IIIA breast cancer who achieved pCR after a short period of neoadjuvant chemotherapy have a satisfactory prognosis and may be suitable for chemotherapy “de-escalation.” This approach is also a dominant application of neoadjuvant “tailoring therapy.”